INTEGRASI KARAKTER MANDIRI BERBASIS QUANTUM LEARNING DALAM PEMBELAJARAN MATEMATIKA DI SMK - Ekayani Khusmawati Syukrillah (Universitas Pekalongan, 2019)
This was a quantitative research with the purpose to achieve mathematics learning that integrating independent character based on quantum learning effectively. The learning was always based on GNNDRC process which are Grow, Nature, Name, Demonstrate, Repeat and Celebrate. This learning method was the strategy on learning by quantum learning-based on. The teaching method was conducted to the 12thgrade students in Ma’arif NU Tirto Vocational School in Pekalongan District. The measured variables were independent character and mathematics literation capability. Observations and tests were the methods to gain the data. The data was analyzed by T test and linear regression. This research shows that integration learning with independent character has reached the effective number. It shows with (1) the students’s literation capability with average score 82,26 statistically has reached the average passing score, (2) the experiment class mathematics literation score is statistically better than the control class score, (3) there is the positive effects of students independence studies to their mathematics literation capability is 31,3%, (4) there is an upgrade of students’s independent character which is 0,63 and it is an average category